A Study of Emotional Intelligence among Malaysian Medical Students in a Public University in Egypt - Md Said, Fatini; A. Samah, Narina; Jaffri, Hadijah (International Journal of Psychosocial Rehabilitation, 2020)
This research was conducted to explore the emotional intelligence among final-year Malaysian medical students in one of the universities in Egypt. Emotional intelligence is often associated with one’s self-efficacy, emotionality, interpersonal skills, and empathic skills. This research was conducted using a qualitative method. Narrative research design was used to gather data from the respondents. Four respondents were chosen by using purposive random sampling. The objective of this study was to explore students’ EI related to self-efficacy and emotionality of final-year Malaysian medical students as they were preparing themselves for a professional exam before being placed in Malaysian public hospitals to complete their housemanship. Semi-structured interview questions were developed and validated before interview sessions were conducted. Content analysis was used to analyze the data obtained from this study. The results were then presented in an inductive content analysis approach. The findings of this study suggested that one’s emotional intelligence would affect one’s career decision-making and coping behavior during emotional distress.